The Perverse Effect of Flexible Work Arrangements on Informality - Edoardo di Porto; Pietro Garibaldi; Giovanni Mastrobuoni; Paolo Naticchioni (Institute of Labor Economics (IZA), 2022)
Flexible work arrangements are on the rise in many countries, ranging from Germany's mini-jobs to UK's zero-hours contracts. These contracts allow for quick labor demand adjustments and are also seen as a way to discourage undeclared work, and more than 10 years ago Italy introduced what was arguably one of the most exible alternative work arrangements: "labor vouchers". The labor vouchers could be easily purchased to pay for occasional work, with no additional paper work. Between 2008 and 2016 the number of 10-euro labor vouchers purchased in a year went up from 500,000 (less than 1 per 100 inhabitants) to almost 300 million (about 5 times the Italian population). Using random timing in labor inspections, as well as the abolition of labor vouchers, we document a perverse effect of badly designed alternative work arrangements: they severely disrupt the work of labor inspectors, allowing firms to increase the amount of undeclared work. Firms who use vouchers for this purpose are shown to hire more regular part-time and fixed-term workers when vouchers become unavailable.
Keywords: J23; H26; 330; informality; labor vouchers; flexible work arrangements; occasional work; zero-hour contracts